Analysis of Firm Value Influenced by Environmental, Social, Governance with Financial Performance as an Intervening Variable - Fredy Olimsar; Wirmie Eka Putra; Feny Tialonawarmi (Institut Bisnis dan Informatika Kesatuan, 2026)
Firm value has shifted from a shareholder-centered view to a broader stakeholder perspective. Investors consider ESG factors alongside financial performance, which remains essential in reflecting a company’s profitability and debt management capacity. This study aims to analyze the effect of environmental, social, and governance on firm value mediated by financial performance. This quantitative study examined companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024. The sample was determined using purposive sampling based on specific criteria. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results of the study indicate that environmental, social, and governance have a significant influence on financial performance. ESG has a significant impact on firm value, indicating that companies with higher levels of ESG coverage tend to have higher firm value. Financial performance significantly influences firm value, indicating that the market values companies that demonstrate stable financial performance. Financial performance partially mediates the relationship between environmental, social, and governance and firm value. These findings imply that companies should integrate ESG practices into their strategic and financial policies to enhance performance and increase firm value in the long term.